Milk Yield, Somatic Cell Count, and Udder Measurements in Holstein Cows at Different Lactation Number and Months - Ayhan Ceyhan; Mahmut Çinar; Ugur Serbester (Faculty of Animal Science, Bogor Agricultural University, 2015)
The aim of this study was to investigate the effect of lactation number and months on milk yield, somatic cell count (SCC) and udder measurements in Holstein cows. In the study, 30 first lactation and 49 second lactation, totally 79 Holstein cows housing in a farm located in Nigde province (Turkey) were used. Somatic cell count and udder measurements were determined at each visit of the farm per months, while lactation milk yield of each animal was calculated using Test Interval Method. It was observed that the effect of lactation number on lactation milk yield (P<0.01) and SCC (P<0.05) was increased significantly. The effect of lactation number on udder measurements was significant (P<0.01) except front teat length (FTD). Influence of lactation months on milk yield and SCC was increased and statistically significant (P<0.01). The effect of lactation months on distance between front teats (DFT), distance between rear teats (DRT), front teat diameter (FTD), rear teat diameter (RTD) was significant (P<0.01). A negative correlation was found between SCC and milk yield, front teat clearance from ground (FTC) and rear teat clearance from ground (RTC). On the other hand, a positive correlation was also evident between RTD and distance between front and rear teats. Furthermore, there were positive correlation between milk yield and DFT, DFR, DRT, and FTD, whereas a negative correlation was observed between milk yield and FTC. In conclusion, cows in second lactation showed importantly increased milk yield and SCC as compared to cows in first lactation, whereas FTC and RTC decreased and other udder measurements increased.Key words: Holstein cow, lactation, milk yield, somatic cell count, udder measurement